2015
DOI: 10.2147/ndt.s73179
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to use highly realistic virtual reality in the elderly? A feasibility study with image-based rendering

Abstract: BackgroundVirtual reality (VR) opens up a vast number of possibilities in many domains of therapy. The primary objective of the present study was to evaluate the acceptability for elderly subjects of a VR experience using the image-based rendering virtual environment (IBVE) approach and secondly to test the hypothesis that visual cues using VR may enhance the generation of autobiographical memories.MethodsEighteen healthy volunteers (mean age 68.2 years) presenting memory complaints with a Mini-Mental State Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 37 publications
(29 reference statements)
4
60
0
3
Order By: Relevance
“…While scores for nausea and oculomotor subscales were higher for the older adult samples compared with younger samples, they were not statistically significant. Previous research has found inconsistent findings when looking at older samples (Kennedy et al, 2010;Benoit et al, 2015). Even though age has been reported as a user characteristic likely to predict motion sickness (Golding, 2006), the results from this review support previous research that there may be a decline in susceptibility to VR sickness as a person ages (Paillard et al, 2013).…”
Section: Age and Vr Sicknesssupporting
confidence: 67%
See 1 more Smart Citation
“…While scores for nausea and oculomotor subscales were higher for the older adult samples compared with younger samples, they were not statistically significant. Previous research has found inconsistent findings when looking at older samples (Kennedy et al, 2010;Benoit et al, 2015). Even though age has been reported as a user characteristic likely to predict motion sickness (Golding, 2006), the results from this review support previous research that there may be a decline in susceptibility to VR sickness as a person ages (Paillard et al, 2013).…”
Section: Age and Vr Sicknesssupporting
confidence: 67%
“…User characteristics adds another layer of complexity in understanding the relationship between hardware, content and VR sickness. Research on sex and age, have generated mixed findings when it comes to the likelihood of sickness from VR (Cheung and Hofer, 2002;Benoit et al, 2015;Munafo et al, 2017;Arcioni et al, 2018). In reference to age, physiological differences over the lifespan (i.e., visual, vestibular senses) (Bermúdez Rey et al, 2016) may influence the occurrence of VR sickness and symptom profiles.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have found more frequent cybersickness symptoms in older adults relative to younger ones, although the reported difference appears to be of a relatively small magnitude (Arns & Cerney, 2005;Liu, Watson, & Miyazaki, 1999). However, a more recent study reported no increase in cybersickness symptoms following immersion in older adults (Benoit et al, 2015).…”
mentioning
confidence: 94%
“…Interestingly, some results suggest that this may not be the case. In a study led by Benoit et al (2015), participants were presented with a photograph or an image-based VR representation of familiar locations in their home city or new locations and were asked to indicate whether they recognised the location. The motivation level of older adults, which was measured with a homemade questionnaire, was found to be larger for the VR than for the non-VR version of the task, although the difference was non-significant.…”
mentioning
confidence: 99%
“…Furthermore, VR systems for cognitive training concentrate on performing activities that are related to IADL, such as: cooking, driving, shopping, etc. The use of a familiar image-based VE can stimulate recollections of autobiographical memory in healthy elderly subjects, as was 131 recently demonstrated (Benoit et al, 2015). The fact that episodic autobiographical memory is impaired in early stages of AD (Seidl, Lueken, Thomann, Geider, & Schorder, 2011), suggests that using such type of VR systems may be helpful for reminiscence rehabilitation of AD patients.…”
Section: Interaction Techniquesmentioning
confidence: 82%